The Influence of Relationship Marketing and Word of Mouth on Patient Loyalty Mediated by Digital Marketing at BC Clinic - Hayuningtias, Ana Tacya; Saparso, Saparso; Fushen, Fushen (Journal Research of Social Science, Economics, and Management, 2026)
This research examines the influence of marketing on patient loyalty at BC Clinic, located in the Cilegon industrial area. Amid fierce competition for healthcare services, it is important for clinics to utilize effective marketing strategies to improve relationships with patients. This study aims to analyze the impact of relationship marketing and word of mouth on patient loyalty, as well as the role of digital marketing as a mediator in these relationships. The method used was a quantitative approach through the distribution of questionnaires to 100 respondents. The collected data were analyzed using the partial least squares (PLS) method to evaluate the relationships between variables. The research also involved descriptive statistical analysis to understand the characteristics of patients and their visit patterns. The results show that relationship marketing has a significant positive effect on patient loyalty, and word of mouth also contributes to increasing loyalty. However, digital marketing did not prove to be an effective mediator in these relationships. These findings provide important insights for BC Clinic in developing a more integrated marketing strategy. Suggestions for BC Clinic include strengthening direct interactions with patients and utilizing positive testimonials to enhance word of mouth. Further research is suggested to explore other influential variables as well as the broader context of health services.